PENGARUH VARIASI KOMPOSISI TERHADAP KARAKTERISTIK PEMBAKARAN BRIKET BIOCOAL BERBAHAN BAKU LIMBAH PERTANIAN - Dwi Aries Himawanto; Supriyadi Supriyadi; Budi Santosa (JURNAL LITBANG PROVINSI JAWA TENGAH, 2009)
The objective of this research is to find the effect of composition variations on the agricultural wastes biocoal briquette. The research is started with heating value analysis and water and ash analysis of agricultural wastes and coal. Then the next step are sizing and mixing that wastes and coal, the research variables are composition of biocoal briquette, the manufactured alternative fuel then take to the furnace to find the combustion characteristic. The result of this research give the best composition i.e 60 % agricultural waste-40 % coal with particle size 20 mesh which bonded with 15 % cassava starch and drying in 110 0C for 90 minutes, which give the best combustion characteristic in the 0 m/s airflow condition.